2023
DOI: 10.1001/jamahealthforum.2023.0245
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Adoption of an Emergency Department Treatment Pathway for Opioid Use Disorder and Patient Initiation of Buprenorphine After Discharge

Abstract: ImportanceEmergency department (ED)–based initiation of buprenorphine has been shown to increase engagement in outpatient treatment and reduce the risk of subsequent opioid overdose; however, rates of buprenorphine treatment in the ED and follow-up care for opioid use disorder (OUD) remain low in the US. The Opioid Hospital Quality Improvement Program (O-HQIP), a statewide financial incentive program designed to increase engagement in OUD treatment for Medicaid-enrolled patients who have ED encounters, has the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Eleven of the 46 articles reported on strategies focusing on substance-related and addictive disorder presentations ( Table 2 ). Four types of strategies were evaluated, including the ED-initiated Medications for Opioid Use Disorder (MOUD) model of care ( 42 45 , 49 52 ), decision support tools ( 42 , 46 , 47 ), ED-initiated social support model of care ( 48 ), and discharge and transfer of care ( 42 , 46 ). Overall, the ED-initiated MOUD model of care reported effects across all four domains of interest; however, not one study reported on all four.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven of the 46 articles reported on strategies focusing on substance-related and addictive disorder presentations ( Table 2 ). Four types of strategies were evaluated, including the ED-initiated Medications for Opioid Use Disorder (MOUD) model of care ( 42 45 , 49 52 ), decision support tools ( 42 , 46 , 47 ), ED-initiated social support model of care ( 48 ), and discharge and transfer of care ( 42 , 46 ). Overall, the ED-initiated MOUD model of care reported effects across all four domains of interest; however, not one study reported on all four.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review found illness-specific strategies oriented to longer-term care delivery beyond the ED, and general mental illness interventions oriented to process improvements. Substance-related and addictive disorder interventions focused on the initiation of initial dose (e.g., buprenorphine or naloxone) with take home doses and clinic follow-up ( 42 45 , 49 52 ). Similarly, strategies for suicide and deliberate self-harm presentations focused on assessment, care plan development and connecting with community-based support ( 53 55 , 58 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations